Studies on some antiatherosclerotic medicinal plants of Bangladesh (Bangladesh Journal of Botany, 2025)
The study investigated the effect of some medicinal plant extracts on atherosclerosis lowering activity in mice model. The results revealed that among the extracts, garlic, ginger and cluster fig reduced cholesterol, triglycerides, and low-density lipoprotein (LDL) cholesterol, but raised the level of high-density lipoprotein (HDL) cholesterol. It is distinctly apparent that the three herb extracts out of the nine herbs studied have anti-atherosclerotic activity.Bangladesh J. Bot. 54(1): 167-170, 2025 (March)